Analisis Peran Kepemimpinan Digital dan Budaya Organisasi dalam Meningkatkan Kinerja Karyawan: Tinjauan Literatur Sistematis - Yunita, Febri Rizma; Isnaini, Santi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The digital era has brought significant changes in organizations, creating a need for effective digital leadership, and adaptation in organizational culture. This transformation not only affects technological aspects, but also impacts how organizations operate. This systematic literature review aims to explore the role of digital leadership and organizational culture that have implications for improvement employee performance in the digital era. Through the Systematic Literature Review (SLR) approach, this study analyzes recent literature on digital leadership, organizational culture, and employee performance in the context of digital transformation. The SLR method is conducted through systematic searches in academic database, study selection based on inclusion and exclusion criteria, data extraction, and synthesis of findings. The results of the review show that digital leadership plays a crucial role in facilitating organizational adaptation to new technologies and driving innovation. Organizational culture that supports digitalization has been found to have a positive impact on employee performance. The interaction between digital leadership and organizational culture creates an environment conducive to increasing productivity, creativity, and employee engagement. Keywords: Transformation, leadership, innovation, and productivity.